Evaluation of an open access generic 3D software for Orthodontic diagnosis and treatment planning - Hany Salah Eldin Eid; Omnia A. Elhiny (Universidade Estadual de Campinas, 2021)
Aim: To evaluate the accuracy and the validity of orthodontic diagnostic measurements, as well as virtual tooth transformations using a generic open access 3D software compared to OrthoAnalyzer (3Shape) software; which was previously tested and proven for accuracy. Methods: 40 maxillary and mandibular single arch study models were duplicated and scanned using 3Shape laser scanner. The files were imported into the generic and OrthoAnalyzer software programs; where linear measurements were taken twice to investigate the accuracy of the program. To test the accuracy of the program format, they were printed, rescanned and imported into OrthAnalyzer. Finally, to investigate the accuracy of editing capabilities, linear and angular transformation procedures were performed, superimposed and printed to be rescanned and imported to OrthoAnalyzer for comparison. Results: There was no statistically significant difference between the two groups using the two software programs regarding the accuracy of the linear measurements (p>0.05). There was no statistically significant difference between the different formats among all the measurements, (p>0.05). The editing capabilities also showed no statistically significant difference (p>0.05). Conclusion: The generic 3D software (Meshmixer) was valid and accurate in cast measurements and linear and angular editing procedures. It can be used for orthodontic diagnosis and treatment planning without added costs.